Effect of fullerene C60 on the melt grafting reaction between multifunctional monomer and polypropylene. Issue 2 (5th June 2012) - Wan, Dong; Xing, Haiping; Zhang, Zhenjiang; Wang, Yujie; Wang, Lu; Wang, Yanhui; Jiang, Zhiwei; Tang, Tao
Abstract Effect of different content of C60 on the melt radical reaction between trimethylol propane triacrylate (TMPTA) and polypropylene (PP) was studied by means of Fourier transform infrared, melt torque values, and rheological results. C60 could transfer most of the reactive PP macroradicals to more stable macroradicals at first due to its higher reaction rate with radicals. Therefore, the homopolymerization of TMPTA was restrained to some extent. PP samples containing TMPTA, C60, and 2, 5‐dimethyl‐2, 5(tert‐butylperoxy) hexane peroxide (DHBP) showed a more obvious influence on increasing the entanglements between PP chains comparing with PP samples containing C60 and DHBP, owing to the synergetic effect between TMPTA and C60 on branching with PP macroradicals. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013